HUBUNGAN KEBIASAAN SARAPAN DENGAN KADAR HEMOGLOBIN (HB) PADA REMAJA PUTRI DI SMA NEGERI 1 RAMBAH TAHUN 2024 - Fitri, Nur Annisa; Fitria, Rahmi; Sulistiawati, Wiwin; Tambunan, Lili Yuliana; Syari, Mila (Jannatul Makwa Health : Jurnal Ilmiah Kesehatan (Scientific Journal of Health), 2025)
Adolescents are one group that is vulnerable to suffering from anemia, especially young women. This is because teenage girls experience menstruation every month. Apart from that, inadequate nutritional intake also causes anemia in young women. Apart from that, the fast-paced activities and lifestyle of teenagers means that nutritional intake in teenagers is insufficient, especially iron. Lack of iron in the blood results in low levels of hemoglobin or red blood cells which can cause anemia. This study aims to examine the relationship between absorption habits and Hb levels of female adolescents at SMA Negeri 1 Rambah, using a cross sectional approach. The population in this study was 376 young women from SMA Negeri 1 Rambah. The sampling technique used in this research is Simple Random Sampling. The results from 80 respondents showed that 55 (68.75%) young women had the habit of eating breakfast, 15 (27.3%) had anemia and 40 (72.7%) did not experience anemia. Meanwhile, of the 25 respondents who did not have the habit of eating breakfast, 14 people (54.2%) had anemia and 11 people (45.8%) did not have anemia. Based on the results of the Chi Square test, a p value of 0.026 (a<0.05) was obtained. This means that the detection of H0 was rejected, meaning that there was a relationship between breakfast habits and Hemoglobin (Hb) levels of young women at SMA Negeri 1 Rambah. In this case it can be concluded that the breakfast habits of young women can influence Hb levels. It is hoped that teaching staff will work together with health workers to increase awareness of young women about the importance of eating breakfast and consuming Fe tablets so that anemia in young women can be managed properly